What is the value of n = 1 ∑ 3 6 0 cos ( 2 n ( n + 1 ) ∘ ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Brilliant, good idea
Let S be the given sum. Then
S ⟹ 2 S S = n = 1 ∑ 3 6 0 cos ( 2 n ( n + 1 ) ∘ ) By reflection k = a ∑ b f ( k ) = k = a ∑ b f ( a + b − k ) = n = 1 ∑ 3 6 0 cos ( 2 ( 3 6 0 − ( n − 1 ) ) ( 3 6 0 − ( n − 2 ) ) ∘ ) Since cos θ = cos ( θ m o d 3 6 0 ∘ ) = n = 1 ∑ 3 6 0 cos ( − ( 2 n − 3 ) 1 8 0 ∘ + 2 ( n − 1 ) ( n − 2 ) ∘ ) and 2 n − 3 is odd = n = 1 ∑ 3 6 0 cos ( − 1 8 0 ∘ + 2 ( n − 1 ) ( n − 2 ) ∘ ) and cos ( − θ ) = cos θ = n = 1 ∑ 3 6 0 cos ( 1 8 0 ∘ − 2 ( n − 1 ) ( n − 2 ) ∘ ) and cos ( 1 8 0 ∘ − θ ) = − cos θ = − n = 1 ∑ 3 6 0 cos ( 2 ( n − 1 ) ( n − 2 ) ∘ ) = − n = 1 cos 0 ∘ − n = 2 cos 0 ∘ − n = 3 ∑ 3 6 0 cos ( 2 ( n − 1 ) ( n − 2 ) ∘ ) = − 1 − 1 − n = 1 ∑ 3 5 8 cos ( 2 n ( n + 1 ) ∘ ) = − 1 − 1 − n = 1 ∑ 3 6 0 cos ( 2 n ( n + 1 ) ∘ ) + cos ( 2 3 5 9 ( 3 6 0 ) ) + cos ( 2 3 6 0 ( 3 6 1 ) ) = − 1 − 1 − S − 1 − 1 = − 4 = − 2
Problem Loading...
Note Loading...
Set Loading...
Let T n = 2 n ( n + 1 ) . Then cos ( T 3 5 9 − n ) = cos ( 2 ( 3 5 9 − n ) ( 3 6 0 − n ) ) = cos ( 1 8 0 ⋅ 3 5 9 − 2 7 1 9 n + 2 n 2 ) = cos ( 1 8 0 ⋅ 3 5 9 − 3 6 0 n + 2 n 2 + n ) = cos ( 1 8 0 + 2 n 2 + n ) = − cos ( 2 n 2 + n ) = − cos ( T n ) . So all but the last two terms in the sum pair off and sum to zero, e.g. cos ( T 1 ) + cos ( T 3 5 8 ) = 0 , cos ( T 2 ) + cos ( T 3 5 7 ) = 0 , etc.
So the sum equals cos ( T 3 5 9 ) + cos ( T 3 6 0 ) = cos ( 1 8 0 ⋅ 3 5 9 ) + cos ( 1 8 0 ⋅ 3 6 1 ) = − 1 + − 1 = - 2 .